LITERATURE REVIEW: EFEKTIVITAS PENDEKATAN TEACHING AT THE RIGHT LEVEL (TaRL) TERHADAP KEMAMPUAN MEMBACA SISWA SD - Aliffya; Norma Helda, Anggun; Habibi, M. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effectiveness of the Teaching at the Right Level (TaRL) approach on the reading ability of elementary school students through a systematic literature review. TaRL is a learning approach that focuses on students' actual ability levels rather than grade levels, developed by Pratham in India and widely adopted in various countries. The method used is a Systematic Literature Review (SLR) with four stages: database identification, title identification, abstract and keyword suitability screening, and selection of reviewed articles. Articles were sourced from three databases Google Scholar, Semantic Scholar, and ERIC published between 2019 and 2024, using Boolean keyword searches. From 1,847 articles found, after a systematic review process, 25 articles met the inclusion criteria and were reviewed. The results show that the TaRL approach is significantly effective in improving students' reading ability, especially for students who are below grade-level reading standards. TaRL is proven to increase reading fluency, comprehension, and early literacy skills through level-based grouping, diagnostic assessment, and targeted instruction. These findings reinforce TaRL's potential as an adaptive and evidence-based instructional strategy for improving reading quality in elementary education.